Faktor-Faktor yang Berhubungan dengan Perilaku dalam Pencarian Pelayanan Kesehatan pada Individu dengan Suspek Tuberkulosis (TB) di Wilayah Kerja UPTD Puskesmas Kota Garo Kabupaten Kampar - Diananta Widola; Wardah Wardah (Journal of Innovative and Creativity (Joecy), 2026)
ABSTRACT The low rate of Tuberculosis (TB) case detection remains a major challenge in TB control because many individuals with presumptive TB do not promptly seek health care. This condition may lead to delayed diagnosis, prolonged disease transmission, and an increased risk of complications. This study aimed to analyze the factors associated with health-seeking behavior among individuals with presumptive TB in the working area of Kota Garo Public Health Center, Kampar Regency. This study employed a quantitative design with a cross-sectional approach. Data were collected from June 1 to June 30, 2026, involving 82 respondents selected using an accidental sampling technique. The research instruments consisted of questionnaires on TB knowledge, community stigma, access to health services, the role of community health volunteers, family support, and health-seeking behavior. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. The results showed that health-seeking behavior and TB knowledge were equally distributed between poor and good categories (50.0% each), a high level of community stigma (56.1%), the role of community health volunteers (54.9%), and family support (52.4%) were predominantly in the good category. Bivariate analysis revealed significant associations between TB knowledge (p = 0.027), community stigma (p = 0.045), access to health services (p = 0.002), the role of community health volunteers (p < 0.001), family support (p < 0.001), and health-seeking behavior. Family support was the strongest associated factor (OR = 7.490). It is recommended that public health centers strengthen community education, enhance the role of community health volunteers, improve access to health services, and involve families in early TB detection efforts ABSTRAK Rendahnya penemuan kasus Tuberkulosis (TB) masih menjadi tantangan dalam pengendalian TB karena banyak individu dengan suspek TB belum segera mencari pelayanan kesehatan. Kondisi tersebut berpotensi menyebabkan keterlambatan diagnosis, memperpanjang rantai penularan, dan meningkatkan risiko komplikasi penyakit. Penelitian ini bertujuan menganalisis faktor-faktor yang berhubungan dengan perilaku pencarian pelayanan kesehatan pada individu dengan suspek TB di wilayah kerja UPTD Puskesmas Kota Garo Kabupaten Kampar. Penelitian ini menggunakan desain deskriptif korelasi dengan pendekatan cross sectional. Pengumpulan data dilaksanakan pada 1 s.d. 30 Juni 2026 terhadap 82 responden yang dipilih menggunakan teknik simple random sampling. Instrumen penelitian menggunakan kuesioner pengetahuan, stigma masyarakat, akses pelayanan kesehatan, peran kader kesehatan, dukungan keluarga, dan perilaku pencarian pelayanan kesehatan. Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square (α=0,05). Hasil penelitian menunjukkan bahwa responden memiliki perilaku pencarian pelayanan kesehatan yang baik (50,0%), tingkat pengetahuan yang baik (50,0%), stigma masyarakat yang tinggi (56,1%), peran kader kesehatan yang baik (54,9%), serta dukungan keluarga yang baik (52,4%). Terdapat hubungan yang bermakna antara pengetahuan (p=0,02), stigma masyarakat (p=0,04), akses pelayanan kesehatan (p=0,00), peran kader kesehatan (p<0,001), dan dukungan keluarga (p<0,001) dengan perilaku pencarian pelayanan kesehatan. Dukungan keluarga merupakan faktor yang memiliki peluang terbesar (OR=7,49). Disarankan puskesmas meningkatkan edukasi masyarakat, memperkuat peran kader kesehatan, meningkatkan akses pelayanan kesehatan, serta melibatkan keluarga dalam upaya deteksi dini TB.